Local Effects of Education and Age Groups on Unemployment in Germany - Fabian Busch; Carsten Ochsen (Growth and Change, 2025)
This article provides a comprehensive analysis of how regional changes in the age and education distribution of the labour force affect local and neighbourhood unemployment rates. Based on theoretical considerations, we argue that differences in job search, separation, and commuting are key factors in group differences, and therefore, changes in relative group size affect the level of unemployment. The empirical analysis focuses on local labour markets in Germany, using a dynamic spatial panel data model. According to the estimates, an increasing proportion of young and/or low-educated workers raises local unemployment, while larger proportions of older prime-age and/or highly educated workers raise unemployment in neighbouring labour markets. As a result, the recent ageing and education developments in the German labour force have led to a 25% reduction in the unemployment rate.
Keywords: 300; ageing; human capital; labour mobility; regional unemployment; spatial interactions